PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) DAN INVENTORY TURNOVER (ITO) TERHADAP NET PROFIT MARGIN (NPM) PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE TAHUN 2018-2022 - Sulistiono, Sulistiono; Nur, Basyiruddin (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
This research purposes to determine the effect of the current ratio, debt to equity ratio and inventory turnover on net profit margins in food and beverage subsector industrial companies listed on the Indonesia Stock Exchange for the 2018-2022 period as many as 10 (ten) companies. This research method uses quantitative with data collection methods using purposive sampling. Disclosure of financial performance, management is expected to improve company performance. The results of this study obtained the results that (1) the significance value of the current ratio is 0.525 greater than 0.05 (0.525 0.05) so that it can be concluded that the current ratio has no effect on the net profit margin; (2) the significance value of the debt to equity ratio is 0.255 greater than 0.05 (0.255 0.05) so it can be concluded that the debt to equity ratio has no effect on the net profit margin; (3) the inventory turnover significant value is 0.677 greater than 0.05 (0.677 0.05) so it can be concluded that inventory turnover has no effect on the net profit margin; (4) Together the significance value of the current ratio is 0.073, the significance value of the debt to equity ratio is 0.050 and the significance value of inventory turnover is 0.346, where the values of the three variables namely the current ratio and inventory turnover have values above 0.05 (0.073 0.05 and 0.346 0.05), while the debt to equity ratio has a value equal to 0.05 so it can be concluded that together the current ratio, debt to equity, and inventory turnover has no effect on the net profit margin.Keywords: current ratio (cr); debt to equity ratio (der); inventory turnover (ito); and net profit margin